FACTORS AFFECTING CUSTOMER SATISFACTION IN INTERNATIONAL HOTELS IN CHENZHOU CITY, CHINA - Yang, Wen Bo; Campos, Maria Rebecca A (PEOPLE: International Journal of Social Sciences, 2020)
The significance of the customer satisfaction management in the hotel industry has been demonstrated by many researchers in the past decades. This study determined the relationship between five key factors (hotel facilities, service capability, service efficiency, service attitude, and breakfast) to the degree of the customer satisfaction with the hotel. These factors were conceptualized from the five dimensions of tangibility, reliability, responsiveness, assurance, and empathy in the SERVQUAL model proposed by Parasuraman, Zeithamal & Berry (1988). Empirical research was conducted in one of the international hotels in Chenzhou City, Hunan Province, China, focusing on the hotel’s customer satisfaction management. The data were taken from the two online reservation websites that reviewed the hotel based on the SERVQUAL model from 2017 to 2018. Multiple linear regression analysis was used to determine the relationship between the five key factors and the degree of customer satisfaction based on about 1,500 online comments. Only two (service capability and service attitude) of the five key factors turned out to have significant positive effects on the customer satisfaction in this hotel. Two other factors (hotel facilities and breakfast) have no significant positive effects, while service efficiency has an unexpected no significant negative effect on this hotel’s customer satisfaction. This study offers some suggestions for improving the future decision-making for the customer satisfaction management of this hotel and also provides a guide for other enterprises experiencing the similar situation with the mutual benefits for avoiding the mistakes in customer satisfaction management so as to improve the overall performance of the hotel.